Technology As A Product Of Science Based On Philosophy - Muhammad Choerul Umam; Siti Masitoh; Mochamad Nursalim (STAIFAS-Press, 2022)
Man defines science and philosophy as a genuine endeavor to comprehend a discipline's approach and notion. The periods' and developments' high needs have ushered philosophy into an arrangement by demonstrating how the